Spatial differentiation of public administration employees due to professional burnout - Bąk, Iwona; Wawrzyniak, Katarzyna (Bulletin of Geography. Socio-economic Series, 2021)
The paper presents the results of the classification of public administration employees from the point of view of the level of occupational burnout, taking into account their place of residence, gender and age. One of the methods of multidimensional statistical analysis - classification trees - was used as a research tool. Two dependent variables are defined. The first one has only two variants defined as: no occupational burnout and occupational burnout, which characterize all the respondents. The second dependent variable was limited to those respondents diagnosed with occupational burnout and has four variants corresponding to the intensity of this burnout. The obtained results indicate the differentiation of voivodships (first-order administrative regions) in terms of the level of the studied phenomenon.